The International Vocabulary of Tinnitus - Baguley, David M.; Caimino, Charlotte; Gilles, Annick; Jacquemin, Laure (Frontiers in Neuroscience, 2022)
Tinnitus is a common experience which can have a severe impact on ones quality of life. Whilst there have been reports of historical references to tinnitus, there has not been an international cross-sectional analysis of the vocabulary used for tinnitus. In this study, with 227 respondents (of which 53.3% experiencing tinnitus themselves), we report such an analysis of 252 words or phrases, from 42 languages and 48 countries. The results indicate that the majority of vocabulary used has a negative connotation (63%), though a small minority are positive (4%). Many words used for tinnitus in different languages are onomatopoeic – thus mimicking aspects of the percept experienced – or describe the sound (in total 42% of the vocabulary). The involvement of the ear is implied in some terminology, though other vocabulary expresses the impact. Participants experiencing tinnitus significantly differed on the codes for their proposed words or phrases (p<.001), with the code “internal suffering or irritation or intrusion” being more prevalent and the code “relate to ear” and ‘sound is phantom or not real or imagined” being less prevalent in this group. This research has implications for the vocabulary used for tinnitus in Patient Reported Outcome Measures, but also, and importantly, for understanding the vocabulary and lived experiences of people with tinnitus by healthcare professionals.